PEDAGOGICAL AND ORGANIZATIONAL CONDITIONS ENSURING THE EFFECTIVENESS OF GOAL-ORIENTED MANAGEMENT OF THE TEACHING STAFF - Muzaffar Ummatovich Kurbanov, (World Scientific Research Journal, 2025)
This article investigates the pedagogical and organizational conditions that support the effective goal-oriented management of teaching staff within educational institutions. Effective management of teaching teams is pivotal in achieving both institutional and systemic educational objectives. The study emphasizes the importance of structured pedagogical processes, enhanced internal communication, and the cultivation of a collaborative culture among educators. Key factors such as leadership competence, motivational climate, and organizational support are identified as determinants of effective management. The article proposes an integrated management model that incorporates pedagogical, psychological, and administrative mechanisms to enhance the productivity, innovation, and professional satisfaction of teaching staff. Practical recommendations for educational leaders are provided to strengthen institutional governance and improve educational outcomes through the coordinated functioning of pedagogical collectives.